Large-scale data analytics - Aris Gkoulalas-Divanis; Abderrahim Labbi (Springer, 2014)
This edited book collects state-of-the-art research related to large-scale data analytics that has been accomplished over the last few years. This is among the first books devoted to this important area based on contributions from diverse scientific areas such as databases, data mining, supercomputing, hardware architecture, data visualization, statistics, and privacy